Tonal alignment in three varieties of Hiberno-English - NI CHASAIDE, AILBHE (ISCA, 2009)
This pilot study investigates the tonal alignment of pre-nuclear (PN) and nuclear (N) accents in three Hiberno-English (HE) regional varieties: Dublin, Drogheda, and Donegal English. The peak alignment is investigated as a function of the number of unstressed syllables before PN and after N. Dublin and Drogheda English appear to a have fixed peak alignment in both nuclear and pre-nuclear conditions. Donegal English, however, shows a drift in peak alignment in nuclear and prenuclear conditions. Findings also show that the peak is located earlier in nuclear and later in pre-nuclear conditions across the three dialects.
PUBLISHED
Keywords: peak alignment; nuclear and pre-nuclear conditions; Hiberno-English